The Role of Productive Waqf in Improving the Economic Welfare of the Community: Legal Study and Implementation in Digital Waqf Institutions Dompet Dhuafa - Istianah; Agustina, Maulida (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study discusses how productive waqf plays a role in improving the community's economic welfare through a legal approach and its implementation in the digital era. Digital transformation has changed how waqf is collected, managed, and distributed. A descriptive qualitative study collected data through literature studies, regulatory documentation, and case studies of digital waqf institutions such as Dompet Dhuafa. A legal approach examines regulations, fatwas, and sharia practices that form the basis for the legality of productive waqf. This approach is used to explore and analyze data from various literature sources relevant to the study's focus, namely productive waqf and its role in improving the economic welfare of the community, especially from the legal side and its implementation in digital waqf institutions. This study examines the legal regulations governing productive waqf and analyzes the real implementation in digital institutions. The study results show that the digitalization of waqf can expand community participation and support the community's economic independence through productive waqf programs. However, challenges in terms of literacy, accountability, and strengthening regulations still need to be addressed.